THE NEED TO DEVELOP INNOVATIVE SKILLS OF FUTURE FINE ARTS TEACHERS - Sardor Mardanaqulovich Abduxamidov (Web of Journals Publishing, 2024)
The article describes the development of the methodology for the development of innovative skills of future visual arts teachers, the need for professional training in the field, creativity skills, and today's demand and necessity
Keywords: image, art, visual arts, innovation, innovative competence, creativity, social, competence, vocational training, skill, improvement, society, social necessity.